Signal characterization and application of UHF RFID system - TAN Xi1; CHANG Ruo-ting2; HUANG Chen-ling1; MIN Hao1 (Tongxin xuebao)
For the asymmetry property of the passive tag UHF RFID system’s up/down link,PIE and FM0/Miller encod-ing were used in the reader and tag baseband respectively.The power spectral density（PSD） and the first null bandwidth of these encoding were characterized by analysis and calculation.The PSD and adjacent channel power ratio（ACPR） of DSB-ASK,SSB-ASK and PR-ASK modulated PIE data after pulse shaping were given by simulation.And the optimized data rate was proposed for a given channel bandwidth.